Because he Was Equal to Kings… Bringing Back the Remains of Juliusz Słowacki in 1927 as Victor Turner’s Social Drama - Mrowiński, Paweł Marek (Vade Nobiscum, tom XXI/2019: Studia z historii gospodarczej, kulturowej i społecznej, 2019)
This article is devoted to one of the largest socio-political spectacles of the Second Polish Republic – bringing the ashes of Juliusz Słowacki to Poland and the re-burial of the poet in June of 1927. The starting point for the analysis of this event is the classical category the rite of passage of Arnold van Gennep, from which the theory of four-act social drama by Victor Turner emerges, in which the spectacle is considered. In addition to the historical background (subsequent attempts to bring the ashes of J. Slowacki to Poland over the decades of the turn of the 19th and 20th centuries), the article indicates the main goals that guided political decision-makers in the mid-1920s wanted to achieve by this event, its role for a new political system in Poland (after May 1926) and its special significance for the Sanation and for Józef Piłsudski himself. In addition to the course of the last journey of Kordian’s author, the text analyzed various elements of the spectacle, and above all, its scenography and its meaning.